2020
DOI: 10.1097/dcr.0000000000001573
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ligation of the Intersphincteric Fistula Tract and BioLIFT for the Treatment of Transsphincteric Anal Fistula: A Retrospective Analysis

Abstract: BACKGROUND: Ligation of the intersphincteric fistula tract is a sphincter-preserving technique for the treatment of anal fistulas. The BioLIFT modification involves the placement of a biologic mesh in the intersphincteric plane. Advocates of this modification state improved healing rates, however evidence for this is lacking, and this approach costs significantly more. OBJECTIVE: The purpose of this study was to compare the healing rates of the ligation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…However, the evidence evaluating these techniques is limited to small studies and such modifications to the standard LIFT technique are typically not recommended. 125,130–134…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the evidence evaluating these techniques is limited to small studies and such modifications to the standard LIFT technique are typically not recommended. 125,130–134…”
Section: Methodsmentioning
confidence: 99%
“…However, the evidence evaluating these techniques is limited to small studies and such modifications to the standard LIFT technique are typically not recommended. 125,[130][131][132][133][134] 9. A cutting seton may be used selectively in the management of complex cryptoglandular anal fistulas.…”
Section: Transsphincteric Fistulas May Be Treated With Ligationmentioning
confidence: 99%
“…However, other authors have recorded rates of 13.9%, 37 11%, 24 and even up to 20%. 45 There is also a huge variation in follow-up time among studies in the literature. A systematic review from Kontovounisios et al 44 reported a decrease in success rates over time, but our results improved slightly from 6-months to 1-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study found the BioLIFT procedure to have a healing rate of 75% in comparison to the standard LIFT procedure at 59%. 52 Despite variable findings for the LIFT procedure, it seems to be a safe and effective surgical treatment option.…”
Section: Ligation Of the Intersphincteric Tract Proceduresmentioning
confidence: 99%